Robust Information Cascade with Endogenous Ordering - ZHANG, Yi (Institutional Knowledge at Singapore Management University, 2016)
We analyze a sequential decision model with endogenous ordering in which decision makers are allowed to choose the time of acting (exercising a risky investment option) or waiting. We show the existence of a unique symmetric equilibrium and characterize information cascade under endogenous ordering. Further, if there are two or more risky investment options, individuals tend to wait longer with competition. Hence, we could end up with a dilemma: more options might be worse.